Sprowadź wyrażenia do najprostszej postaci:

a) 13e - 5(f - 3e) =
b) 4(-2r + s) - 10,5r =
c) -3(3x - 2y) + 2(x - 2y) =
d) -5(2z - 3y) - 4(4z - 2y) =
e) 2(2p - 3q + 7) - 3(p - 2q + 4) =
f) 2(3x² - 2y + 5y²) - 3(4y + 5y²) + 2x - 3x² =x

dam naj ;D

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-07T15:01:24+01:00
A) 13e - 5(f - 3e) = 13e - 5f + 15e = 28e - 5f
b) 4(-2r + s) - 10,5r = -8r + 4s - 10,5r = -18,5r + 4s
c) -3(3x - 2y) + 2(x - 2y) = -9x + 6y +2x -4y = -x-4y
d) -5(2z - 3y) - 4(4z - 2y) = -10z + 15y - 16z + 8y= 23y -26z
e) 2(2p - 3q + 7) - 3(p - 2q + 4) = 4p - 6q + 14 - 3p + 6q -12 = 2 + p -9q
f) 2(3x² - 2y + 5y²) - 3(4y + 5y²) + 2x - 3x² = 6x² -4y + 10y² - 12y - 15y² = 6x² - 16y -5y²
2 5 2
2010-01-07T15:03:11+01:00
A) 13e-5(f-3e)=13e-5f+15e=28e-5f

b) 4(-2r+s)-10,5r=-8r+4s-10,5r=-18,5r+4s

c) -3(3x-2y)+2(x-2y)=-9x+6y+2x-4y=-7x+2y

d) -5(2z-3y)-4(4z-2y)=-10z+15y-16z+8y=23y-26z

e) 2(2p-3q+7)-3(p-2q+4)=4p-6q+14-3p+6q-12=p+2

f) 2(3x²-2y+5y²)-3(4y+5y²)+2x-3x²-x=6x²-4y+10y²-12y-15y²+2x-3x²-x=3x²-5y²+x-16y
  • Użytkownik Zadane
2010-01-07T15:03:24+01:00
A) 13e - 5(f - 3e) =13e-5f+15e=28e-5f
b) 4(-2r + s) - 10,5r=-8r+4s-10,5r=-18,5r+4s
c)-3(3x - 2y) + 2(x - 2y) =-9x+6y+2x+2y=-7x+8y
d) -5(2z - 3y) - 4(4z - 2y) = -10z + 15y - 16z + 8y= 23y -26z
e) 2(2p - 3q + 7) - 3(p - 2q + 4) = 4p - 6q + 14 - 3p + 6q -12 = 2 + p -9q
f) 2(3x² - 2y + 5y²) - 3(4y + 5y²) + 2x - 3x² = 6x² -4y + 10y² - 12y - 15y² = 6x² - 16y -5y²